Peripapillary choroidal thickness by enhanced depth imaging optical coherence tomography: the impact of metabolic syndrome - Loureiro, Monica (2017)
Purpose: To assess the impact of metabolic syndrome (MetS) on the peripapillary choroidal thickness (PPCT) and to characterize the PPCT in a Portuguese population.Methods: This prospective study included 104 eyes. Detailed medical and ophthalmic examinations were performed; the PPCT was measured by spectral-domain optical coherence tomography (SD-OCT) using enhanced depth imaging (EDI) modality. The PPCT changes with MetS, as well as with other clinical and demographic factors, were investigated.Results: The mean PPCT was 142.4 +/- 54.0 mu m (58-303 mu m); it was thickest superiorly, followed by the temporal, nasal, and inferior sectors. The PPCT was significantly associated with axial length (p<0.001), age (p=0.001), intraocular pressure (IOP) (p=0.041), weight (p=0.015), and arterial hypertension (p=0.044). The presence of MetS was associated with thinner PPCT in all sectors, being statistically significant in the temporal (p=0.032) and inferotemporal (p=0.034) sectors.Conclusions: The choroidal thickness was significantly less in temporal and inferotemporal sectors in patients with MetS than in controls. This may suggest vascular insufficiency around the optic nerve head.